(untitled) (Relevant Tomorrow / Aktualu rytoj, 2025)
The article reflects on the opportunities and challenges that tools of the digital humanities pose for researchers in the field of cultural heritage and memory. The reflections are based on the project “The Cultural and Intellectual Geography of the Former Polish Lands after the Partitions, 1865–1918: A Digital Vademecum” (hereinafter, the Vademecum Project). The project’s goal is to collect and share data on selected aspects of broadly defined cultural heritage from the multi-ethnic territory of the former Polish–Lithuanian Commonwealth during the period 1865–1918. The article has shown that the Vademecum Project interacts with memory institutions. On the one hand, it draws upon their heritage and resources and on the other hand, it complements their mission (based on historical sources, it provides information about missing publications, destroyed monuments, or lands long since confiscated). The project has also revealed that the use of digital tools in heritage and memory studies poses many challenges—ranging from assembling an interdisciplinary team and organizing its effective work to finding suitable methodological and technical solutions where two such distinct fields as the humanities and computer science intersect. However, the opportunities and prospects offered by this type of collaboration outweigh risk factors. Amid the many threats that the modern world poses, the Vademecum Project (and other similar projects) has the task of preserving cultural heritage and creating memory. Constantly evolving digital tools and technological advances are indispensable in this mission.